2006
DOI: 10.1300/j395v02n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Cotton Materials Using Corona Discharge

Abstract: The present work concerns the study of preparation processes when this operation is preceded by a CORONA discharge made on dry raw fabrics. The influence in the whiteness degree, hydrophility, starch removal and uniformity of properties of the cellulosic material after preparation is studied.Combined preparation processes are widely used in order to replace solutions where desizing, alkaline boiling and bleaching are individual operations, being a main interest to find the optimal conditions to achieve alkalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In two surveys conducted by Carneiro et al it was possible to observe a considerable increase in the quality of preparation of cotton fabrics treated with DBD plasma in air. According to the authors, the increase in hydrophilicity observed after DBD treatment becomes crucial in textile desizing, alkaline boiling, bleaching, dyeing, printing and finishing processes . The effect of plasma discharge on the bleaching of grey cotton fabric has also been studied by varying power discharge and number of discharges.…”
Section: Desizingmentioning
confidence: 99%
See 1 more Smart Citation
“…In two surveys conducted by Carneiro et al it was possible to observe a considerable increase in the quality of preparation of cotton fabrics treated with DBD plasma in air. According to the authors, the increase in hydrophilicity observed after DBD treatment becomes crucial in textile desizing, alkaline boiling, bleaching, dyeing, printing and finishing processes . The effect of plasma discharge on the bleaching of grey cotton fabric has also been studied by varying power discharge and number of discharges.…”
Section: Desizingmentioning
confidence: 99%
“…The plasma treated fabrics dyed with three direct dyes, have proven to be a valid alternative to the classical method of processing cotton fabrics. Several other studies of the same authors have revealed that plasma treatment of cotton results in improving dyeability due to the creation of micro‐channels for water penetration . Another research evaluates the differences between the functionalization obtained on the surface of cotton fibres with corona plasma, and the chemical cationization of the cotton fibres with an epihalohydrin by means of a dyeing process with a bifunctional reactive dye.…”
Section: Dyeingmentioning
confidence: 99%
“…Some of the treatments, such as hydroxylamine treatment and plasma discharges, are used for surface pretreatment of fabrics [24,25]. Plasmatic treatments in several textile substrates like cotton, linen, wool and synthetic fibers were studied proving that this type of treatment increases whiteness degree, removal of waxes and sizing agents, absorption and fixation of dyes and finishing agents, improves durability of functional effects and is able to provide certain functional groups available to bind PN [26][27][28][29][30]. Alay et al [31] studied the effect of plasma treatment of cotton fabrics on fluorocarbon-based water-repellent finishing.…”
mentioning
confidence: 99%
“…The changes in the surface modification and chemical configuration of the dyed fabrics upon application of plasma have been studied [90][91][92][93][94]. The particular exposure time, applied voltage, feed gas, etc., contribute to the enhancement of dyeability [95][96][97]. When textiles are treated with plasma, it undergoes significant physical and chemical changes like changes in layers of the surface, structural, and physical properties.…”
Section: Cap For Textile Industrymentioning
confidence: 99%